An Insight into Risk Identification, Quality and Productivity Enhancement using Six Sigma - Muhammad Usman Tariq (Journal of Education and Vocational Research, 2011)
Six Sigma, with a myriad of its applications in numerous organizational and business processes, offers a project management methodology that supports achieving a goal of near perfection in process performance. Six Sigma is based on the impetus of Plan-Do-Check-Act can help industries, businesses and organizations to achieve significant performance improvement as most of the Fortune 500 companies have adopted Six Sigma (DeFeo & William, 2004). Six Sigma initiatives primarily entail DMAIC and DMADV methods for attaining a high standard of quality. In this paper we provide a critical analysis of the various Six Sigma applications, techniques and tools that can be used for improving quality and productivity of the organizations. The study also provides an insight into the methods used for risk identification in Six Sigma. The proposed techniques are evaluated and analyzed viz-a-viz DMAIC and DMADV approaches. The objective of this research is to summarize the existing level of research in the field of Six Sigma and highlighting the need for intensive academic research in this area. The study comparatively analyzes Six Sigma with Lean, QFD, PSP/TSP, FMEA, TPRM, AHP/ISS and PMBOK requirements. The study also highlights the prospective areas of future/further research in this discipline. The critical analysis of various techniques studied as part of this research reveals that Six Sigma is primarily beneficial for process improvement, risk identification and management etc. The critical analysis of this study is reported herein.